2008
DOI: 10.1080/10715760802555569
|View full text |Cite
|
Sign up to set email alerts
|

Redox balance following magnetic stimulation training in the quadriceps of patients with severe COPD

Abstract: In severe COPD patients, oxidative stress, which is involved in their peripheral muscle dysfunction, increases in response to exercise. In this study, muscle oxidative stress was explored after quadriceps magnetic stimulation training. A randomized controlled study was conducted on very severe COPD patients, who underwent quadriceps magnetic stimulation training for 8 weeks. A control group was also studied. In both groups, vastus lateralis specimens were obtained before and after the 8-week period. Muscle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…These results have potential clinical implications in the management of patients with chronic lung diseases and muscle dysfunction including COPD, especially in the design of specific exercise training programs. Indeed, it has been clearly demonstrated that both the intensity and length of the training programs are of paramount importance to improve exercise capacity, muscle function, biology, and structure in those patients (17,21,58,68,80).…”
Section: Epigenetic Regulation Of Muscle Adaptation To Environmental mentioning
confidence: 99%
“…These results have potential clinical implications in the management of patients with chronic lung diseases and muscle dysfunction including COPD, especially in the design of specific exercise training programs. Indeed, it has been clearly demonstrated that both the intensity and length of the training programs are of paramount importance to improve exercise capacity, muscle function, biology, and structure in those patients (17,21,58,68,80).…”
Section: Epigenetic Regulation Of Muscle Adaptation To Environmental mentioning
confidence: 99%
“…Differences in the protein carbonyl content among several samples reflect their resistance or susceptibility to oxidative stress. In this regard, different studies from several groups including our own have demonstrated increases in the levels of protein carbonylation as well as identification using proteomics analyses in tissues under different conditions [14,15,16,17,18,19,23,30,31,32,34,35,36,40,41,61,62,63,64,65,66,67,68]. Indeed, protein oxidation has been shown to play a crucial role in the pathophysiology of multiple disorders such as degenerative diseases, aging, atherosclerosis, cancer, and skeletal muscle dysfunction associated with acute and chronic conditions [14,41,69,70].…”
Section: Production Of Oxidants and In Vivo Protein Carbonylationmentioning
confidence: 99%
“…For instance, the vastus lateralis muscle of patients with severe COPD consistently exhibits a slow-to-fast fiber type switch [18,19,123]. Nonetheless, in the same patients, a fast-to-slow fiber type transformation takes place in the diaphragm of patients with identical disease severity [14,23,88,123,124,125,126].…”
Section: Protein Carbonylation In Skeletal Muscle Dysfunction and mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, defined as the imbalance between oxidants and antioxidants, and as measured by several markers, such as protein oxidation and nitration and lipid peroxidation, has been consistently shown in blood and limb muscles of patients with severe COPD both at rest and after exercise 33,35,51,[54][55][56][57][58][59][60][61] . Importantly, oxidative stress markers were also shown to inversely correlate with several…”
Section: Quadriceps Muscle Dysfunctionmentioning
confidence: 99%